Pembuatan Profil Media Sosial Usaha Mikro Kecil Menengah (UMKM) Fresh Milk di Desa Balunganyar - Citra Oktavina Eka Lidyawati; Rafico Rifki Febrian; Safika Safika; Rahayu Mardikaningsih; Didit Darmawan; Mila Hariani; Arif Rachman Putra; Agung Satryo Wibowo (CV. Aksara Global Akademia, 2025)
The creation of social media profiles for Micro, Small, and Medium Enterprises (MSME) Fresh Milk in Balunganyar Village is an essential strategy for enhancing competitiveness and market reach in the digital era. This MSME relied solely on limited traditional promotion methods; however, by establishing a presence on platforms such as Instagram and Facebook, Fresh Milk has successfully expanded its consumer reach and increased sales. Social media also facilitates direct interaction with customers, thereby enhancing trust and consumer loyalty. Challenges such as limited knowledge of digital marketing strategies and intense competition still need to be addressed. The aim of this research is to improve the social media profile of the fresh milk MSME to attract consumer attention and boost sales. The method used is Asset-Based Community Development (ABCD), focusing on identifying the assets owned by the MSME and empowering the community through training. With guidance from students of UNSURI, the Fresh Milk business owners received training on effective social media management, including branding, content creation, and utilizing customer feedback for product development. In the long term, this program is expected not only to increase sales but also to strengthen brand awareness and inspire other MSME in Balunganyar Village to adopt digital technology in their marketing strategies. The results of the program indicate that social media is a highly effective tool for the development of MSMS today.